1996
DOI: 10.1073/pnas.93.9.4251
|View full text |Cite
|
Sign up to set email alerts
|

A general assay for antibody catalysis using acridone as a fluorescent tag.

Abstract: 177.9, 141.6, 133.8, 131.7, 127.9, 124.1, 122.4, 121.1, 114.3, 44.6, 36.8, 33.6, 30.9, 25.7, 25.4, 19.5, 17.7(3'S,6'S) 10-[(3 ',7')-Dimethyl-(6',7')-epoxyoct-1 '-yl] -9-(10H)-acridone (Compound 2a) and (3'S,6'R)10-[(3',7')-dimethyl-(6',7')-epoxyoct-1'-yl] -9(1OH)-acridone (Compound 2b). Sodium bicarbonate (100 mg) and m-chloroperbenzoic acid (250 mg of 50-60% suspension in water) were added to a solution of olefin 1 (210 mg; 0.63 mmol) in dichloromethane (6 ml). After 2 hr at 20°C, the solution was washed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Acridone, used as a tag in fluorescence-based assays, [30,31] has been grafted as a pendant arm on macrocyclic cyclen-based ligands by Faulkner's group [27] in order to sensitize Eu III luminescence. Advantages of such a heterocycle include its chemical inertness, its remarkable resistance to photobleaching and, above all, the possibility to be excited around 400-420 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Acridone, used as a tag in fluorescence-based assays, [30,31] has been grafted as a pendant arm on macrocyclic cyclen-based ligands by Faulkner's group [27] in order to sensitize Eu III luminescence. Advantages of such a heterocycle include its chemical inertness, its remarkable resistance to photobleaching and, above all, the possibility to be excited around 400-420 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological function of these receptors is therefore currently unknown and requires further work. Other fruitful avenues of research may also use acridone and 5-TAMRA conjugated ligands as these are highly photostable and have been used for confocal and high resolution techniques such as two photon excitation (Banala et al, 2012;Puliti et al, 2011;Reymond et al, 1996). Thiazole orange (TO) is known to selfquench owing to stacking, but emits light when the stacking is disrupted by binding (Lukinavi cius and Johnsson, 2011;Volkova et al, 2008), a property that we found preliminary evidence of when using our ligand G-TO (unpublished data).…”
Section: Supports Thismentioning
confidence: 99%
“…We have reported a highly sensitive assay based on analyzing reactions of substrates labeled with the fluorescent tag acridone by thin-layer chromatography. [5] Although generally applicable, the above-mentioned assays are used in practice as single point measurements of product formation. However the ideal setup for catalysis screening involves continuous monitoring of product increase in solution.…”
Section: Introductionmentioning
confidence: 99%